2016
DOI: 10.1177/1059840516641189
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Asthma Management as Identified by School Nurses

Abstract: Asthma rates are increasing in children. School nurses have opportunities to care for children with asthma but need to overcome barriers impacting their ability to manage asthma in the school setting. This study (a) assessed barriers present in the school setting, (b) determined the impact of barriers on performance of asthma management behaviors, and (c) determined the impact of barriers on importance ratings of asthma management behaviors, asthma self-efficacy, and asthma attitudes (N = 537). Results reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…Research must move toward understanding existing school nurse practice modelsincluding staffing mix and how it affects both nursing and student outcomes. Quaranta & Spencer (2016) address the barriers school nurses face in asthma management, which may support an investigation into staffing practices. Winkelstein et al (2006) encourage a complete understanding of school nurses' needs, which can lead to the successful implementation of asthma education in their work settings.…”
Section: Discussionmentioning
confidence: 99%
“…Research must move toward understanding existing school nurse practice modelsincluding staffing mix and how it affects both nursing and student outcomes. Quaranta & Spencer (2016) address the barriers school nurses face in asthma management, which may support an investigation into staffing practices. Winkelstein et al (2006) encourage a complete understanding of school nurses' needs, which can lead to the successful implementation of asthma education in their work settings.…”
Section: Discussionmentioning
confidence: 99%
“…Institutional resources recently reported as barriers include limited Wi-Fi access for required modern technology such as continuous glucose monitoring (March et al, 2020). Financial issues related to keeping necessary supplies in stock and hiring staff were also obstacles in school health care services (Kao et al, 2018;Quaranta & Spencer, 2016;Seki et al, 2017).…”
Section: Institutional Level Barriersmentioning
confidence: 99%
“…Additionally, school nurses reported a lack of intangible materials, such as resources developed by school nurses or teachers, for providing school health care as a barrier. A lack of educational resources for students (Quaranta & Spencer, 2016), such as access to age-appropriate asthma education materials (Carpenter et al, 2017), was also identified as a barrier in school health services.…”
Section: Institutional Level Barriersmentioning
confidence: 99%
“…One relevant aspect for this is self-efficacy, which is an individual’s belief in his/her own ability to perform a specific action to manage a particular situation [ 12 , 13 ]. Furthermore, self-efficacy is essential for managing asthma [ 14 , 15 , 16 ] and for medication adherence in general [ 17 ].…”
Section: Introductionmentioning
confidence: 99%